اردو ناول میں بیانیہ کی تکنیک - Dr, Sumaira Akbar; Dr. Abdul Uzair Malik; Dr. Rabia Sarfaraz (Khayaban - خیابان, 2023)
The term Narrative is widely used today in literature as well as in politics, religion, culture, history and the media. Narrative is a piece of writing that tells a story, Narrative is an essential part of fiction. Under the influence of narrative, characters, scenes, dialogues and other elements of the story are formed. Narrative is actually a fictional paradigm. An important element of narrative is the narrator. In fiction, the narrator is the person who tells the story. There can be two forms of narrator in Urdu novel First person narrator and Third person narrator. Symbol, Epistolary, Stream of consciousness, Flash back, Flash Forward, Internal monologue, Magic realism and Anti novel are some techniques of Narrative in Urdu Novel.